What is "grazing"? Reviewing its definition, frequency, clinical characteristics, and impact on bariatric surgery outcomes, and proposing a standardized definition - Conceição, Eva Martins (2014)
Background: Grazing, characterized by a repetitive eating pattern, has received increased attention among bariatric surgery patients. However, different definitions and terminology have been used, preventing the accurate measurement of this phenomenon and comparison of data across studies.Objective: To review existing definitions and associated clinical features of grazing among different samples and to propose a standardized definition that will allow for consistency in future work. Setting: University and Clinical Research Institute.Methods: Of the 39 studies found, 9 provided an original definition and 12 provided data of its association with weight outcomes. Six were studies of nonbariatric surgery populations. Based on this literature review, the most common criteria used in previous studies to define grazing were included in a survey that was sent to 24 individuals who have published work in the field. These experts were asked to provide their opinion on what should constitute grazing.Results: Grazing is a frequent behavior in the bariatric surgery population as well as in eating disordered and community samples. Its association with psychopathology is not clear, but its negative impact on weight outcomes after bariatric surgery generally has been supported. Survey data provided a consensus regarding the definition of grazing as an eating behavior characterized by the repetitive eating (more than twice) of small/modest amounts of food in an unplanned manner, with what we characterize as compulsive and noncompulsive subtypes.Conclusions: Given the clinical relevance of grazing among bariatric surgery patients, a unique definition is crucial to better study its associated features and impact on different populations. (C) 2014 American Society for Metabolic and Bariatric Surgery. Published by Elsevier Inc. All rights reserved.